The Influence of Anxiety and Depressive Symptoms During Pregnancy on Birth Size. Issue 2 (24th November 2013) - Broekman, Birit F. P.; Chan, Yiong‐Huak; Chong, Yap‐Seng; Kwek, Kenneth; Cohen, Sung Sharon; Haley, Charlotte Louise; Chen, Helen; Chee, Cornelia; Rifkin‐Graboi, Anne; Gluckman, Peter D.; Meaney, Michael J.; Saw, Seang‐Mei; et al.
Abstract Background Mental health problems during pregnancy can influence fetal growth. However, studies examining the influence of maternal mental health across the normal range of birth outcomes are uncommon. This study examined the associations between symptoms of maternal depression and anxiety during pregnancy on birth size among term Asian infants. Methods One thousand forty‐eight Asian pregnant women from a cohort Growing Up in Singapore Towards Healthy Outcomes were recruited between 2009 to 2010 at two Singaporean maternity hospitals. At 26 weeks gestation, depressive symptoms were measured with the Edinburgh Postnatal Depression Scale (EPDS) and the Beck Depression Inventory II (BDI‐II), and anxiety was measured with the Spielberger State‐Trait Anxiety Inventory (STAI). Health personnel recorded birthweight, birthlength, gestational age, and head circumference at birth. Results Nine hundred forty‐six women who delivered term infants had complete data. For this sample, the mean birthweight was 3146.6 g [standard deviation (SD) 399.0], the mean birthlength was 48.9 cm (SD 2.0). After controlling for several potential confounders, there was a significant negative association between STAI and birthlength [β = −0.248, confidence interval (CI) [−0.382, −0.115], P < 0.001] and a small negative association between EPDS and birthlength (β = −0.169, CI [−0.305, −0.033], P = 0.02). No associations were found between scores on the EPDS, BDI‐II, and STAI with birthweight or head circumference. Conclusions Our preliminary data suggest that among term infants, anxiety and depressive symptoms are not associated with birthweight, while anxiety and depressive symptoms are associated with a shorter birthlength.